Payments for the conservation of animal genetic resources in agriculture - Juvančič, Luka; Slabe-Erker, Renata; Ogorevc, Marko; Drucker, Adam G.; Erjavec, Emil; Bojkovski, Danijela (2021)
Financial incentives for the conservation of local breeds are intended to make breeding and keeping more economical. Fixed payments per livestock unit (LU) are common. A study from Slovenia was pub-lished in March in the journal “Animals”, 2021, 11, which examined how state subsidies for the conser-vation of animal genetic resources affect population numbers and how farmers react.